Mechanistic investigation of the NH-sulfoximination of sulfide. Evidence for λ6-sulfanenitrile intermediates. Issue 12 (30th January 2017) - Lohier, Jean-François; Glachet, Thomas; Marzag, Hamid; Gaumont, Annie-Claude; Reboul, Vincent
Abstract : One-pot synthesis of NH-sulfoximines from sulfides was reported through fully described acetoxy- and methoxy-λ 6 -sulfanenitrile intermediates ( 1 H, 13 C, 15 N NMR and HRMS). Abstract : We report a new procedure for the preparation of NH-sulfoximines from sulfides using PIDA as an oxidant and ammonium carbamate as the ammonia source. Excellent yields were obtained with a wide range of sulfides. The formation of acetoxy- and methoxy-λ 6 -sulfanenitrile as intermediates was proposed, both of which were converted to the NH-sulfoximine by the action of the solvent. The structure of these intermediates was confirmed by 1 H, 13 C and 15 N NMR and HRMS analysis.